PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERDASARKAN MODEL PEMBELAJARAN APTITUDE TREATMENT INTERACTION (ATI) PADA SUB POKOK BAHASAN PRISMA DAN LIMAS KELAS VIII SMP - Lestari, Novi Dwi; Hobri, H; Trapsilasiwi, Dinawati (Kadikma, 2014)
Abstract. Aptitude Treatment Interaction (ATI) is a concept which has some instructional strategies (treatments) that are optimally effective for students of different aptitude levels.This research is expected to know the process and result of the development of mathematics learning instruments based on Aptitude Treatment Interaction (ATI) in sub subject of Prism and Pyramid. The subject of the research is students of grade VIII A SMP AL-Muttaqin Banjarsengon Jember. Learning instrumentsdevelopment model refers to Thiagarajan, Semmel and Semmel Model (4-D) Model.The result product is lesson plan, student books, work sheets, and evaluation test. Based on validation process and tryout the learning sets can be concluded that the learnig sets had been appropriate with validate, practice, and effective criteria. Key Words:Aptitude Treatment Interaction (ATI), Set 4-D Model